2020
DOI: 10.3390/ma13194433
|View full text |Cite
|
Sign up to set email alerts
|

Primary Stability of Orthodontic Titanium Miniscrews due to Cortical Bone Density and Re-Insertion

Abstract: The increasing demand for orthodontic treatment over recent years has led to a growing need for the retrieval and reuse of titanium-based miniscrews to reduce the cost of treatment, especially in patients with early treatment failure due to insufficient primary stability. This in vitro study aimed to evaluate differences in the primary stability between initially inserted and re-inserted miniscrews within different cortical bone densities. Artificial bone was used to simulate cortical bone of different densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Hand-held micromotion measurement devices such as PTV and IST are portable and easy to use and have become popular tools for the evaluation of miniscrew micromotion. Previous research has indicated that micromotion is affected by the cortical bone density and porosity, which supports the findings of the current study [ 18 ]. However, the accuracy of these non-invasive easy-to-operate methods for evaluating primary stability is still debated [ 17 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Hand-held micromotion measurement devices such as PTV and IST are portable and easy to use and have become popular tools for the evaluation of miniscrew micromotion. Previous research has indicated that micromotion is affected by the cortical bone density and porosity, which supports the findings of the current study [ 18 ]. However, the accuracy of these non-invasive easy-to-operate methods for evaluating primary stability is still debated [ 17 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…The porosity of the polyurethane foam blocks was measured via micro-computed tomography (CT) (SkyScan 1076, Kontich, Belgium) ( Figure 2 ). According to previous studies [ 14 , 17 , 18 ], the artificial bone comprised a 2 mm layer of higher density (30, 40, and 50 pcf) polyurethane foam representing cortical bone, and a 20 mm layer of lower density (20 pcf) polyurethane foam representing cancellous bone ( Figure 1 B). Miniscrews were implanted into the artificial bone at different depths (3, 4, 5, and 6 mm) ( Figure 1 C) using an automatic torque device (Admet eXpert8600, ADMET, Norwood, MA, USA) to control the insertion depth [ 19 ].…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations